2022
DOI: 10.3390/buildings12010078
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms and Parameters of Elastoplastic Deformations of Anchorage in a Damaged Concrete Base under Seismic Loading

Abstract: The article addresses mechanisms of anchorage failure in a concrete base studied within the framework of physical experiments. The authors investigated the most frequently used types of anchors, such as the cast-in-place and post-installed ones. The anchorages were studied under static and dynamic loading, similar to the seismic type. During the experiments, the post-earthquake condition of a concrete base was simulated. Within the framework of the study, the authors modified the values of such parameters, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Effects of the anchor head size and the concrete member thickness are investigated by Nilforoush et al 4 Specific aspects of non-standards concrete material properties are presented with respect to aggregate type in the study by Ninčevi c et al, 5 curing state in the study by Ninčevi c and colleagues, [6][7][8] the influence of low-emission concrete binders in the study by Al-Yousuf and colleagues, 7,9 and the inclusion of fiber reinforcement in the study by Spyridis and Mellios. 10 Beyond typical quasi-static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, [13][14][15][16] and fire. [17][18][19][20] The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an indepth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load-bearing capacity of anchors against breakout failure, are discussed for cast-in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post-installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete.…”
Section: Behavior Of Anchors In Tension Subject To Concrete Cone Failurementioning
confidence: 99%
“…Effects of the anchor head size and the concrete member thickness are investigated by Nilforoush et al 4 Specific aspects of non-standards concrete material properties are presented with respect to aggregate type in the study by Ninčevi c et al, 5 curing state in the study by Ninčevi c and colleagues, [6][7][8] the influence of low-emission concrete binders in the study by Al-Yousuf and colleagues, 7,9 and the inclusion of fiber reinforcement in the study by Spyridis and Mellios. 10 Beyond typical quasi-static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, [13][14][15][16] and fire. [17][18][19][20] The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an indepth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load-bearing capacity of anchors against breakout failure, are discussed for cast-in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post-installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete.…”
Section: Behavior Of Anchors In Tension Subject To Concrete Cone Failurementioning
confidence: 99%
“…The main objective was to consider failure mechanisms and the effect of the type of anchors on the crack width. A widely used earthquake-resistant anchors were considered within the scope of th (a) Cast-in-place anchors (e.g., L-shaped anchors), embedded in a 3.0 mm wide crack, are beyond the scope of the study, because no reduction in the bearing capacity and no change in the stress-strain behavior of embedded anchors are identified in cracks whose width is below 1.5 mm [32].…”
Section: Crack Openingmentioning
confidence: 99%
“…To simulate seismic loading, the anchorage was subjected to increasing multi-cycle dynamic loading until the anchorage failure according to one of the failure mechanisms listed in the studies [32]. A total of four failure mechanisms were identified (see Table 3).…”
Section: Anchormentioning
confidence: 99%
See 2 more Smart Citations